Herpetology of an antique land: the history of herpetological explorations and knowledge in India and south Asia - Das, I. (The Research Institute, 2004)
The history of herpetological explorations in the Indian subcontinent is traced from Vedic times to present. The profound knowledge that the ancients of India had ca. 3,300 years before present, including the identification and classification of snakes, was remarkable, and probably stems from their deep interest in the natural world, besides the obvious utilitarian value of such knowledge. Medieval European knowledge of the regional herpetofauna consisted mostly of exaggerated accounts culled from beastiaries and colourful accounts by visitors writing primarily for the entertainment of a European audience. With the Mughal period came the age of natural history record keeping. Many of the rulers were keen natural historians and kept memoirs that often recorded specific information on amphibians and reptiles.